PERAN ETIKA KERJA HINDU DALAM PENINGKATAN KINERJA SUMBER DAYA MANUSIA PADA ERA REVOLUSI INDUSTRI 5.0 - Mahayasa, I Gede Aryana; Abiyoga Wulandari, Ni Luh Adisti; Sumandi, Ni Komang (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.03.TAHUN.2022, 2022)
This examination expects to decide the impact of Hindu work ethics in the connection between locus of control and performance. The exceptionally fast changes and improvements in innovation in the 5.0 time changed human conduct rapidly as well. This examination was directed on all LPDs in Denpasar City, adding up to 35 units. The information was gathered through perception, meetings, surveys, and writing study. The results showed that the locus of control and Hindu work ethics attitudes had a positive and huge impact on the presentation of the LPDs Director in Denpasar City. The association between factors locus of control and Hindu work ethics attitudes expresses that Hindu hard working attitudes assume a part in fortifying the impact of locus of control on the presentation of the LPDs Executive in Denpasar City. So that in the advancement of HR in the LPDs, it is important to zero in on moral conduct dependent on the upsides of the lessons of the Hindu religion to accomplish authoritative objectives just as to construct respectable, respectable, and decent individuals.